Some procedures for solving special max-min fractional rank-two reverse-convex programming problems - Ionac, Doina; Ţigan, Ştefan (Rev. Anal. Numér. Théor. Approx., 2004)
In this paper we suggest some procedures for solving two special classes of \(\)-\(\) fractional reverse-convex programs. We show that a special bilinear fractional max-min reverse-convex program can be solved by a linear reverse-convex programming problem. For a linear fractional max-min reverse-convex program, possessing two reverse-convex sets, we propose a parametrical method. The particularity of this procedure is the fact that the max-min optimal solution of the original problem is obtained by solving at each iteration two linear reverse-convex programs with a rank-two monotonicity property.